Subjective changes in nasal patency after chewing a menthol-containing gum in patients with olfactory loss. (March 2014) - Schriever, Valentin A; Hummel, Thomas
Abstract Conclusion: The subjective increase in nasal patency after oral menthol application depends on olfactory function. In patients with relatively low olfactory sensitivity, this effect is small or absent. It was hypothesized that this may also modulate the sensation of nasal blockage. Objective: Menthol stimulates the nasal trigeminal nerve, resulting in a subjectively increased nasal airflow and patency without objectively measurable changes. Patients suffering from olfactory impairment also express a reduced nasal trigeminal sensitivity. The aim of this investigation was to examine the effect of menthol on nasal patency ratings in a group of patients suffering from olfactory dysfunction. Methods: A group of 92 patients with olfactory impairment was included in this study. Olfactory function was assessed using the 'Sniffin' Sticks.' Patients were instructed to chew a menthol-containing gum for 30 s, after which they rated the change in nasal patency on a categorical scale. Results: Patients who rated the change in nasal patency as pronounced scored higher on the Sniffin' Sticks olfactory test compared to patients who experienced little or no change in nasal patency after chewing the menthol-containing gum. On average, similar changes could be observed for all etiologies of olfactory impairment included in this study.